Demographic responses of nearly extirpated endangered mountain caribou to recovery actions in Central British Columbia. Issue 5 (5th June 2022) - McNay, R. Scott; Lamb, Clayton T.; Giguere, Line; Williams, Sara H.; Martin, Hans; Sutherland, Glenn D.; Hebblewhite, Mark
Abstract: Recovering endangered species is a difficult and often controversial task that challenges status quo land uses. Southern Mountain caribou are a threatened ecotype of caribou that historically ranged in southwestern Canada and northwestern USA and epitomize the tension between resource extraction, biodiversity conservation, and Indigenous Peoples' treaty rights. Human‐induced habitat alteration is considered the ultimate cause of caribou population declines, whereby an increased abundance of primary prey—such as moose and deer—elevates predator populations and creates unsustainable caribou mortality. Here we focus on the Klinse‐Za and Quintette subpopulations, part of the endangered Central Group of Southern Mountain caribou in British Columbia. These subpopulations were trending toward immediate extirpation until a collaborative group initiated recovery by implementing two short‐term recovery actions. We test the effectiveness of these recovery actions—maternity penning of adult females and their calves, and the reduction of a primary predator, wolves—in increasing vital rates and population growth. Klinse‐Za received both recovery actions, whereas Quintette only received wolf reductions, providing an opportunity to test efficacy between recovery actions. Between 1995 and 2021, we followed 162 collared female caribou for 414 animal‐years to estimate survival and used aerial counts to estimate population abundance and calf recruitment. We combined these data in an integrated population model to estimate female population growth, total population abundance, and recovery action effectiveness. Results suggest that the subpopulations were declining rapidly (λ  =  0.90–0.93 ) before interventions and would have been functionally extirpated (<10 animals) within 10–15 years. Wolf reduction increased population growth rates by ~0.12 for each subpopulation. Wolf reduction halted the decline of Quintette caribou and allowed them to increase (λ  =  1.05 ), but alone would have only stabilized the Klinse‐Za (λ  =  1.02). However, maternity penning in the Klinse‐Za increased population growth by a further ~0.06, which when combined with wolf reductions, allowed populations to grow (λ  =  1.08). Taken together, the recovery actions in these subpopulations increased adult female survival, calf recruitment, and overall population growth, more than doubling abundance. Our results suggest that maternity penning and wolf reductions can be effective at increasing caribou numbers in the short term, while long‐term commitments to habitat protection and restoration are made.